Building Excellent Human Resources through Merdeka Belajar Kampus Merdeka in Era 5.0 - Rony, Zahara Tussoleha; Widodo, Aan; Lestari, Tyastuti Sri; Saimima, Ika Dewi Sartika; Ismaniah, Ismaniah; Mursito, Kendhy (International Journal of Social Science and Business, 2024)
Welcoming the era of Society 5.0, through the program "Merdeka Belajar Kampus Merdeka," universities are expected to transform the higher education system as the driving force for creating superior human resources for the nation's future. This study aims to explain the dynamics of the independent learning program activities at the independent campus across seven faculties at Bhayangkara University, Jakarta. The research adopts a post-positivist paradigm with a case study approach, involving 25 informants and five key informants. Secondary data were obtained from the Sistem Pembelajaran Daring - Kementerian Riset, Teknologi, dan Pendidikan Tinggi (SPADA DIKTI), which includes a compilation of data from students, lecturers, and education staff. Primary data were collected through interviews, observations, and documentation studies related to the implementation of the Merdeka Belajar Kampus Merdeka program. The data were analyzed descriptively using manual data analysis procedures. The results indicate that most faculties and study programs have not yet optimally explained the flow, program procedures, and complete infrastructure used in implementing the program. However, most students and lecturers acknowledge that the program is highly beneficial and critical for developing quality human resources for the future.